Reframing higher education sustainability through dynamic environmental, foresight strategy, and value creation program: Voices from educational experts - Hindarwati, Enny Noegraheni; Rahayu, Agus; Gaffar, Vanessa; Wibowo, Lili Adi (Universitas Jambi, Indonesia, 2026)
This study aims to develop a performance framework for higher education institutions in developing countries that is aligned with the Sustainable Development Goals (SDGs) agenda. A qualitative approach using an in-depth interview model was employed to identify the main dimensions from the perspectives of purposively selected educational management experts. The research was conducted over 61 days, with core activities consisting of in‑depth interviews via the Zoom Meeting platform, and thematic analysis was adopted. The findings indicate that a performance design for higher education institutions in developing countries that is consistent with the SDGs agenda must, at a minimum, exhibit three key dimensions: a dynamic environment, a foresight strategy, and a value-creation program. All three must be firmly anchored in the Tridharma of Indonesian higher education. These results are highly valuable, as they offer a conceptual contribution by integrating the discourse on education for sustainability, higher education governance, and the SDGs framework into a comprehensive, contextually grounded performance model for the provision of higher education in developing countries.